Evaluasi Usability Website Program Studi Sistem Informasi Universitas Jambi Menggunakan System Usability Scale (Sus) - Andreansyah, M. Arif; Suratno, Tri; Willy Bima Alfajri (JUSS (Jurnal Sains dan Sistem Informasi), 2026)
A study program website is the main channel for delivering academic information and serves as the institution's digital representation, so its usability is essential to ensure effective service delivery. This study aims to evaluate the usability of the Information Systems Study Program website at Universitas Jambi using the System Usability Scale (SUS) method. Data were collected through an online questionnaire distributed to website users, namely students and lecturers, using a purposive sampling technique. Of the 34 questionnaires collected, 32 were declared valid after a data-validity verification process and were used for analysis. The results show that the website obtained an average SUS score of 64.92, placing it in Grade C with an "OK" adjective rating and a Marginal acceptability level. This value is below the commonly cited SUS benchmark of 68, indicating that the website's usability is fair but has not yet reached the acceptable category. Item-level analysis shows that the weakest aspects are learnability, interface consistency, and user independence, while overall ease of use and functional integration were rated favorably. Based on these findings, improvements to the navigation structure, design consistency, and feature accessibility are recommended to enhance the website's usability quality.